2009
DOI: 10.4141/cjps08005
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in performance of Canadian-bred apple cultivars and implications for breeding

Abstract: K. 2009. Regional differences in performance of Canadian-bred apple cultivars and implications for breeding. Can. J. Plant Sci. 89: 81Á91. To evaluate their commercial potential in several major production regions of Canada, 10 Canadian breeding selections and two standard cultivars of apple (Malus )domestica Borkh.) were planted at four locations: one in British Columbia, two in Ontario and one in Nova Scotia. Subsidiary objectives of the trial were to determine whether wider testing of promising apple select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Hampson et al (2009) also showed that the effect of G × E on growth and yield traits of 11 advanced apple selections was minimal. Although the BV estimates, which are the sum of effects across a number of loci, might be relatively similar across different environments, it does not necessarily mean that the effects at an individual locus will also be similar.…”
Section: Genotype × Environment Interaction (G × E)mentioning
confidence: 90%
“…Hampson et al (2009) also showed that the effect of G × E on growth and yield traits of 11 advanced apple selections was minimal. Although the BV estimates, which are the sum of effects across a number of loci, might be relatively similar across different environments, it does not necessarily mean that the effects at an individual locus will also be similar.…”
Section: Genotype × Environment Interaction (G × E)mentioning
confidence: 90%
“…There are numerous apple germplasm collections that have been established worldwide (e.g., USA (Gross et al, 2013), China (Gao et al, 2015), New Zealand (Kumar et al, 2010), and Europe (Jung et al, 2020)). Within Canada, there are apple collections located across the country, for example, in Ontario and British Columbia (Hampson et al, 2009;Ward, 1978). Most recently, Canada's Apple Biodiversity Collection (ABC) was established in Nova Scotia, Canada, with over 1,000 accessions that includes trees primarily belonging to the domesticated apple, M. domestica, and its primary wild ancestor, M. sieversii.…”
Section: Introductionmentioning
confidence: 99%
“…The variation could also be the result of phenotypic characteristics of the varieties, management practices and the site of the plantation (Bhat et al, 2006 andHampson et al (2009). This variation could be due to the phenotypic characteristics of the cultivars, management practices.…”
Section: Resultsmentioning
confidence: 99%